Rheumatoid Arthritis-Associated Autoimmunity Due to Aggregatibacter actinomycetemcomitans and Its Resolution With Antibiotic Therapy - Mukherjee, Amarshi; Jantsch, Vanessa; Khan, Rida; Hartung, Wolfgang; Fischer, René; Jantsch, Jonathan; Ehrenstein, Boris; Konig, Maximilian F.; Andrade, Felipe (Frontiers in Immunology, 2018)
Objective: We describe a 59-year-old man with a diagnosis of anti-citrullinated protein antibody (ACPA)-positive rheumatoid arthritis (RA) who presented for evaluation of refractory RA. He was found to have infective endocarditis due to Aggregatibacter actinomycetemcomitans (Aa), a bacterial species recently linked to RA pathogenesis. Following antibiotic therapy, joint symptoms resolved and ACPAs normalized. Because of this striking clinical scenario, we further investigated the bacterial, genetic and immune factors that may have contributed to the patient’s clinical and autoimmune phenotypes. Methods. DNA was extracted from serum and used to amplify the Aa leukotoxin (ltx) promoter region by PCR, which was further analyzed by Sanger sequencing. High-resolution identification of HLA alleles was performed by sequenced based typing. TNF-α, IFN-γ, IL-18, IL-1β, IL-17A, GM-CSF, IL-6, IL-8, IL-21, and IL-22 were quantified in serum by a multiplex immunoassay. IgG and IgA antibodies to Aa leukotoxin A (LtxA) were assayed by ELISA. Results. Aa genotyping confirmed infection with a highly leukotoxic strain carrying a 530-bp ltx promoter deletion. Immuno-phenotyping showed elevation of Th1/Th17 cytokines, anti-LtxA antibodies and host susceptibility conferred by three HLA alleles strongly linked to ACPAs and RA (DRB1*04:04, DRB1*15:01, and DPB1*04:01). One year after Aa eradication with antibiotic therapy, the patient remained free of joint symptoms and anti-CCP antibodies. Conclusion. In the context of genetic risk for RA, systemic subacute infection with Aa can drive ACPA production and a clinical phenotype similar to RA.